2018
DOI: 10.13031/trans.12646
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Emissions from Dairy Lagoons in the Western U.S.

Abstract: Ammonia (NH 3 ) emissions from dairy liquid storage systems can be a source of reactive nitrogen (N) released to the environment, with a potential to adversely affect sensitive ecosystems and human health. However, little on-farm research has been conducted to estimate these emissions and determine the factors that may affect these emissions. Six lagoons in south-central Idaho were monitored for one year using open-path Fourier transform spectrometry, with NH 3 emissions estimated using inverse dispersion mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
(52 reference statements)
2
13
0
Order By: Relevance
“…These results are consistent with Leytem et al. (2018), who observed higher CH 4 emission fluxes in warmer than cooler periods. They attributed the higher fluxes to higher microbial activity in the wastewater systems.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with Leytem et al. (2018), who observed higher CH 4 emission fluxes in warmer than cooler periods. They attributed the higher fluxes to higher microbial activity in the wastewater systems.…”
Section: Resultssupporting
confidence: 93%
“…According to Barbera et al (2019), thermophilic methanogens thrive well between 4 and 100 ˚C but are more active at higher temperatures. These results are consistent with Leytem et al (2018), who observed higher CH 4 emission fluxes in warmer than cooler periods. They attributed the higher fluxes to higher microbial activity in the wastewater systems.…”
Section: Ambient Temperature and Influent Conditionssupporting
confidence: 93%
“…Comparing IFSM simulations of feed production and intake, fossil energy use, and production costs with actual records for the US Meat Animal Research Center showed differences of less than 1% during the study year of 2011 (Rotz et al, 2013). Numerous other studies have verified the model's ability to represent feed crop production, animal performance, emissions, and other components of the model in dairy production (e.g., Belflower et al, 2012;Rotz et al, 2014;Bonifacio et al, 2015;Jego et al, 2015;Leytem et al, 2018).…”
Section: Modeling Proceduresmentioning
confidence: 87%
“…The 270-300 • sector dominated the wind direction at IGIA (Acharja et al, 2021). Figure 5a shows that the highest NH 3 concentration was associated with the winds coming from the east and southeast of the site, where it could have been emitted from dairy farms, including animal houses, yards, and manure storage, as well as by the application to the farmland of urea and other ammoniacal fertilizers, ammoniacal wastes, and ruminant urine located at this region (Hindustan Times, 2021;Leytem et al, 2018;Sherlock et al, 1994). Such sources of NH 3 volatilization (Hristov et al, 2011;Laubach et al, 2013) can also explain the higher concentrations of total NH + 4 (and, by definition, NH x ) for air coming from the southeast of the measurement site (Fig.…”
Section: Gas-to-particle Partitioningmentioning
confidence: 99%